EFFECTS OF DIGITAL PROGRAMS ON THE LEVEL OF FORMATION OF DIGITAL SKILLS OF THE STUDENTS - Baitasheva, Gaukhar; Mussina, Aitzhamal; Medeuova, Galiya; Umbettulla, Ayaulym; Zhamanbayeva, Karlygash (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2025)
Global changes in information, communication, professional, and other spheres of modern society necessitate several adjustments in educational practices. In preparing integrated tasks, students are taught to apply knowledge from various subjects to solve specific problems. One of the most important conditions for enhancing the effectiveness of the educational process is the development of students’ research and digital skills, which in turn fosters their creative and logical thinking abilities. This study employed a quasi-experimental research design. The sample consisted of 46 second-year chemistry-biology students (23 in each group) from the Kazakh National Women’s Teacher Training University during the second semester of the 2022-2023 academic year. The experimental and control groups were randomly selected. Key findings include a 7.7% improvement in digital skills among the experimental group compared to the control group (a high level of 48.3% in the experimental group, compared to 40.6% in the control group). The verification of integrated tasks indicates that digital skills involve understanding the purpose, conditions, and means of action. These skills are aimed at researching and clarifying specific processes, facts, and phenomena, while effectively utilizing knowledge and life experience. This research contributes novel insights by demonstrating how integrated tasks enhance digital competency within a chemistry-biology curriculum. The findings suggest that incorporating such methodologies into educational frameworks can bridge the gap between theoretical knowledge and practical application, ultimately improving students’ readiness for the digital economy and research-oriented careers.